Determination of shelf life time of cured guinea pig meat (Cavia porcellus L.) using different concentrations of sodium chloride - Rodríguez Barrionuevo, Pedro Zacarías (2017)
Therefore in this research the shelf life time of vacuum-packed cured guinea pig meat using different concentrations of sodium chloride was determined and the effects produced sodium chloride on the proximal chemical composition of guinea pig meat cured were evaluated, giving a longer shelf life time, the analytical methods used were: pH, TBA value, water activity, microbiological tests: aerobic mesophilic count, Staphylococcus aureus, Salmonella sp. and Escherichia coli. For proximal chemical evaluation were performed tests of % moisture, % ash, % protein and% fat, making a comparison between the 1% concentration of sodium chloride with a standard sample (C0%). Based on the results it was observed that the concentration of sodium chloride 1% provided greater shelf life 12 days compared to concentrations of 3% and 5% sodium chloride they showed lifetime of 10 and 8 days respectively. Regarding the proximal chemical composition the concentration 1% sodium chloride it gave a moisture content of 68.21 %, a percentage of ash of 2.11 %, a percentage of protein 11.04 % and a percentage of fat of 6.34 % compared the master batch (C0 %) presented a percentage of 69.07 % moisture, ash percentage 0.85 %, a percentage protein and percentage 14.85 6.73 %. As in the proximal chemical composition, it was observed that sodium chloride had a significant effect on the percentage of ash and protein; however the percentage of moisture and fat did not differ significantly. The results indicate that sodium chloride has a significant effect on the shelf life time of vacuum-packed cured guinea pig meat.